Pemanfaatan Kulit Ubi Jalar Ungu (Ipomoea batatas) Terhadap Intensitas Warna pada Ikan Guppy (Poecilia reticulata) - Mita Alvionita; Sutianto Pratama Suherman; Arif Maulana Abduh (Universitas Mataram, 2025)
Guppy fish (Poecilia reticulata) is one of the freshwater ornamental fish species with high economic value, in which body color quality and intensity are the main factors determining attractiveness and market value. Color intensity in ornamental fish is influenced by natural pigments that largely cannot be synthesized endogenously and therefore must be obtained through diet. One potential source of natural pigment is purple sweet potato peel (Ipomoea batatas), which contains high levels of anthocyanins and is environmentally friendly. This study aimed to analyze the effect of purple sweet potato peel (Ipomoea batatas) solution supplementation on the color intensity of guppy fish (Poecilia reticulata). Guppy fish have high economic value, making color quality an important factor in increasing their commercial appeal. Purple sweet potato peel contains anthocyanin pigments that can be utilized as a natural colorant source in ornamental fish feed. The study was conducted for 30 days at the UMKM Perkumpulan Aquaculture Kasih Karunia Suwawa, Bone Bolango Regency, Gorontalo Province. The experimental design used was a Completely Randomized Design (CRD) with four treatments and three replications, namely P0 (control without solution), P1 (5 ml/100 g feed), P2 (10 ml/100 g feed), and P3 (15 ml/100 g feed). Observed parameters included color intensity, absolute length and weight growth, survival rate (SR), feed conversion ratio (FCR), and water quality. The results showed that treatment P3 produced the highest increase in color intensity compared to other treatments, although the differences were not statistically significant (p > 0.05). The best FCR value was obtained in treatment P1, while the highest survival rate was observed in treatment P3. Based on these results, it can be concluded that supplementation of purple sweet potato peel solution has the potential to enhance the color intensity of guppy fish and can be utilized as an alternative natural colorant in ornamental fish culture. y.